2017
DOI: 10.24042/jipfalbiruni.v6i2.1743
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Pemahaman Konsep Vektor pada Siswa Sekolah Menengah Atas

Abstract: Penelitian ini bertujuan untuk mengungkap pemahaman konseptual tentang vector, siswa kelas XI SMA di Kabupaten Natar, Lampung Selatan. Populasi adalah seluruh siswa kelas XI SMA dari tujuh SMA dan jumlah sampel sebanyak 167 siswa. Data dikumpulkan dengan menggunakan 15 soal pilihan jamak dan alasan pertanyaan yang dibutuhkan. Hasil penelitian menunjukkan bahwa hanya 39,1% siswa yang mengerti tentang konsep vektor. Vektor satuan adalah subtopik yang paling mudah dipahami dimana 61,1% siswa memahami subtopik sed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 2 publications
1
8
0
8
Order By: Relevance
“…The majority of the students had no functional understanding of Newton's second law as a relationship between vectors. The results of this study are consistent with the results of previous studies which suggest that most students have difficulty regarding vectors (Sari, Suyanto, & Suana, 2017) and their application in solving the problem of Newton's law of motion (Flores et al, 2004). To overcome such difficulties, (Flores et al, 2004) suggest that the content and sequence, of course, topics should be adapted to the target, i.e., the development of students' skills in understanding vectors and their application in mechanical systems.…”
Section: Discussionsupporting
confidence: 89%
“…The majority of the students had no functional understanding of Newton's second law as a relationship between vectors. The results of this study are consistent with the results of previous studies which suggest that most students have difficulty regarding vectors (Sari, Suyanto, & Suana, 2017) and their application in solving the problem of Newton's law of motion (Flores et al, 2004). To overcome such difficulties, (Flores et al, 2004) suggest that the content and sequence, of course, topics should be adapted to the target, i.e., the development of students' skills in understanding vectors and their application in mechanical systems.…”
Section: Discussionsupporting
confidence: 89%
“…Pendidikan adalah usaha-usaha yang direncanakan untuk mewujudkan proses pembelajaran yang menyenangkan dan efektif (Latifah, 2015;Rahmaniati & Supramono, 2015 (Sari, Suyanto, & Suana, 2017…”
Section: Pendahuluanunclassified
“…The tendency of student research variables leads to the mastery of the concept with a percentage of 31.53%; this is relevant to the statement by (Duit, 2007) that the focus of the object of research is understanding the concept of learners. Mastery of the concept itself indicates how learners (research subjects) capture the main information (essence) of physics learning (Sari, Suyanto, & Suana, 2017). Based on the background of students' research, the mastery of the concept is chosen to be the research variable based on the issues of physics learning found in the majority field using mathematical approach.…”
Section: Research Variablesmentioning
confidence: 99%